Somatic phraseological units of European and Oriental languages - Pacsai Имре (Turkic Studies Journal, 2022)
. Studying phraseological units is important task of linguistics, which is confirmed by the results of research by well-known scientists. This study compare the specific elements of European and Eastern phraseology which connected with cultural and linguistics traditions. The works of N. S. Trubetskoy motivated our research, as he revealed the influence of the Turkic and Finno-Ugric languages on the Russian language and Russian culture. In the study of the semantics and structure of phraseological units in Eastern languages, we found their semantic and structural similarities with the phraseological units of the Hungarian language. This article discusses some somatisms (the name of a part of the human body) in the phraseological units of European and Oriental languages, their differences are noted, due to the mental and cultural traditions of the peoples; the semantic and structural similarities of phraseological units of the Hungarian and Turkic, Oriental languages, associated with historically areal, linguistic and cultural contacts, are revealed. Somatisms in the Turkic and Hungarian languages, in addition to the direct designation of a part of the human body (head, heart, eye, ear, hand, etc.), also have figurative meanings that express the spiritual world of a person, his positive or negative characteristics. These figurative meanings are also found in phraseological units of the Chinese language. Structurally, somatisms in the phraseological units of the Turkic, Finno-Ugric, Hungarian, and Chinese languages are represented by complex paired words, which confirms their certain typological commonality. Paired somatisms in the phraseology of the Russian language are due to the arealcultural influence of the Turkic and Uralic languages.